2019
DOI: 10.1002/rsa.20845
|View full text |Cite
|
Sign up to set email alerts
|

Uniform random colored complexes

Abstract: We present here random distributions on (D+1)-edge-colored, bipartite graphs with a fixed number of vertices 2p. These graphs encode D-dimensional orientable colored complexes. We investigate the behavior of those graphs as p → ∞. The techniques involved in this study also yield a Central Limit Theorem for the genus of a uniform map of order p, as p → ∞.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…A motivation for the study of triangulations comes from the discretization of space in quantum gravity, see [3,17]. Recently there has been a renewed interest in this topic via coloured tensor models, which are a higher dimensional generalization of matrix integrals, see [14,8]. The objects that naturally arise in these models are coloured triangulations: roughly speaking, a triangulation is coloured if the vertices are coloured with colours from 1 to d + 1, and all colours appear in each d-simplex.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A motivation for the study of triangulations comes from the discretization of space in quantum gravity, see [3,17]. Recently there has been a renewed interest in this topic via coloured tensor models, which are a higher dimensional generalization of matrix integrals, see [14,8]. The objects that naturally arise in these models are coloured triangulations: roughly speaking, a triangulation is coloured if the vertices are coloured with colours from 1 to d + 1, and all colours appear in each d-simplex.…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…Since vertices of X(G) are in bijection with connected components of 3-coloured subgraphs of G, there exist distinct colours i, j, k such that κ i,j,k ≥ Kn 4 log n . By (8) with I = {i, j, k} and up to relabelling i, j, k, we have κ i,j − κ i,j,k ≤ n 6 − 1 3 κ i,j,k ≤ n 6 − Kn 12 log n .…”
Section: Remaining Proofsmentioning
confidence: 99%
“…Given the last two lemmas, the proof of Corollary 3 is rather straightforward. Indeed, combining (8) and (9) we deduce that with probability at least 1 − 2ε all vertices of ConfigModel(U 2n ) are linked to V δn are linked to each other. Hence the diameter of the graph is less than 3 and we even have d gr (u, v) 2 as soon as u or v has degree larger than A.…”
Section: P All Vertices With Degreementioning
confidence: 99%
“…• one distinguished white vertex (resulting from the contraction of the root-edge). 7 In [26], constellations were called stacked maps, as a central quantity in that work was the sum of faces over a certain set of submaps. Here we use the term constellations, as it is a common name in the combinatorics literature for (the dual) of these objects.…”
Section: Bijection With Constellationsmentioning
confidence: 99%
“…Still, fixing the order of the graph is responsible for the a.a.s. non-singular topology of the building block (in [7], it is shown that a uniform (q + 1)-colored graph with q > 2 and all of its residues are a.a.s. dual to pseudo-manifolds with singularities).…”
Section: Topological Structure Of Large Random Syk Graphs Of Fixed Ordermentioning
confidence: 99%